OVERVIEW OF HEALTH CHARACTERISTICS OF BLOOD PRESSURE, CHOLESTEROL, URIC ACID AND BLOOD SUGAR LEVELS IN AN-NUR WOMEN'S MARINDAL VILLAGE 1 KEC. PATUMBAK KAB. DELI SERDANG - Diah Lestari; Fatwa Imelda; Febrina Oktavinola Kaban (Talenta Publisher, 2019)
Non-communicable diseases are quite serious public health problems and require more comprehensive and multidisciplinary care. The high mortality rate caused by heart disease, stroke, gout and diabetes mellitus is caused by unhealthy eating patterns, unhealthy habits, lack of physical activity and stress. Indonesia is the 4th country with people with diabetes mellitus after China, India and the USA. Hypertension or high blood pressure is a cause of increased risk of stroke, heart and kidney. The number of Majelis Taklim assemblies and Pengajian can be used maximally by health workers to socialize health programs in improving community health status. Perwiritan An-Nur, Marindal Village 1 Kec. Patumbak Kab. Deli Serdang is thought to have a high risk of non-communicable diseases such as hypertension, stroke, gout and diabetes mellitus. Observation of the habits of the community has an unhealthy lifestyle. This community service carried out 2 activities namely promotion and prevention with 30 samples. Educational activities are education about hypertension, stroke, gout and diabetes mellitus as well as activities. Preventive activities include checking cholesterol, uric acid and blood sugar levels. From the results of the implementation of community service found the majority of respondents aged> 50 years as many as 22 people (27%), the majority of low levels of education 17 people (57%), the majority do not work 27 people (90%), the majority of Javanese 20 people (67% ), the majority of married women 28 people (93%) and the majority with a history of passive smoking as many as 20 people (67%), the majority of normal blood pressure as many as 21 people (70%), the majority of normal cholesterol levels as many as 27 people 27 (90%) , the majority of normal uric acid levels were 26 people (87%), the majority of normal blood sugar levels were 28 people (93%). To improve health status and reduce the incidence of non-communicable diseases by conducting counseling and health checks.